If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+7x=-x
We move all terms to the left:
3x+7x-(-x)=0
We add all the numbers together, and all the variables
3x+7x-(-1x)=0
We add all the numbers together, and all the variables
10x-(-1x)=0
We get rid of parentheses
10x+1x=0
We add all the numbers together, and all the variables
11x=0
x=0/11
x=0
| a/14=-3 | | T+5=-t-9 | | (2/3)(x)=1/6 | | 4f(0)=5(0)–(0)^2 | | 5|-2x-3|-10=25 | | −16t^2+30t=4 | | 16x+5=67.5 | | -3b+5=-4b | | 1/2z+6=3/2{z+6} | | (2y)+(3y+10)=70 | | x/3.4+4.3=22 | | −10x=−25−x2 | | 106=15x-4 | | 5g+20=2g-7 | | 10-6q=-8q | | 22=x/6 | | 5.)-7+x=-7 | | 10x+9=3(4x+7) | | -7+x=-76.) | | 8=0x+8 | | 105+15x=180 | | 46+100+x=180 | | -3w-9=-2w | | 17^3x-1=21 | | 90=x+39(2x) | | 0.5x+x+4=13 | | (5.5/t)=0.5 | | 17c+2=25 | | (2x+-4=6- | | x²-5x+0=0 | | 17l+2=25 | | 11=x+3/3 |